Graphite oxide coated alumina composite material synthesized through chemical bond induction and having high stamping mechanical strength, and preparation method and application thereof
Through chemical bond-induced synthesis, alumina and graphite oxide are modified by acid solution etching and high-temperature oxidation to form an oxygen-rich graphite-coated alumina composite material, which solves the problem of reduced mechanical strength of alumina materials and significantly improves the Mechanical strength and stability of the catalyst.
Patent Information
- Application Number
- CN202411743456.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-30
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Due to the rich pore structure, the mechanical strength of alumina materials decreases during the molding process, resulting in the breaking of the catalyst and affecting the progress of the catalytic reaction.
Through the method of chemical bond-induced synthesis, the surface of alumina particles is etched with acid solution to form chemical group defects, and polar oxygen-containing groups are introduced to the surface of graphite oxide by instantaneous high-temperature oxidation to form oxygen-rich graphite oxide. Then, oxygen-rich graphite oxide is coated on the alumina particles, and the mechanical strength is increased by chemical bonding or cross-linking.
The mechanical stamping strength of the alumina support is significantly improved, forming a uniform surface structure, and enhancing the stability and use performance of the catalyst.
Smart Images

Figure CN119455928A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of supported catalyst carriers, and in particular to a graphite oxide-coated aluminum oxide composite material with high stamping mechanical strength synthesized by chemical bond induction. Background Art
[0002] At present, there are various types of supported catalyst carriers, among which alumina is a catalyst carrier with great potential. Alumina can withstand various harsh environments such as high temperature, high pressure, acid and alkali, and maintain the activity and stability of the catalyst. At the same time, the high-temperature alumina catalyst carrier has a stable specific surface area and a good pore structure, which is conducive to the dispersion of active components and the catalytic reaction. Graphite oxide has a strong stamping mechanical strength and is usually used to assist in the mechanical stamping strength of modified alumina materials when used as catalyst carriers, so that alumina carriers have broad application prospects in the fields of petrochemicals, automobile exhaust purification, environmental governance, and fine chemical synthesis.
[0003] However, alumina materials often have rich pore structures, which leads to reduced mechanical strength during the process of synthesizing and preparing alumina particles. When alumina particles are used as catalyst carriers, the poor mechanical strength will cause the catalyst to break, thereby affecting the catalytic reaction. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a graphite oxide-coated alumina composite material with high stamping mechanical strength synthesized by chemical bond induction, a preparation method and application thereof. The prepared composite material has the characteristics of regular morphology, good uniformity and no pores on the surface.
[0005] The object of the present invention is achieved by: a method for preparing a graphite oxide-coated alumina composite material with high stamping mechanical strength synthesized by chemical bond induction, comprising the following steps: S1. Dissolve aluminum salt in deionized water, stir to obtain solution A, add ammonia water to solution A, let stand, filter to obtain aluminum hydroxide powder, and calcine the aluminum hydroxide powder in a tube furnace under air atmosphere to obtain aluminum oxide powder; S2, adding an inorganic binder to the alumina powder, kneading it for multiple times, placing it in an extruder, drying and calcining it to obtain alumina particles; S3, etching the hydroxyl groups on the surface of the aluminum oxide particles by an acid solution to obtain aluminum oxide particles with chemical group defects; S4, adding graphite powder and sodium nitrate to the acid solution under ice-water bath conditions, slowly adding potassium permanganate, stirring, heating in a water bath to a certain temperature, and maintaining, to obtain a mixed solution B; S5, adding deionized water and a strong oxidant to the mixed solution B cooled to room temperature until no bubbles are generated, centrifuging, washing, and drying to obtain dark yellow graphite oxide; S6. Disperse graphite oxide in an alcohol solution, introduce polar oxygen-containing groups into the graphite oxide (polar solid-affinic groups) by instantaneous high-temperature oxidation to obtain graphite oxide in an oxygen-rich state on the surface.
[0006] S7, dispersing aluminum oxide particles with hydroxyl group defects in a deionized water solution, adding oxygen-enriched graphite oxide, allowing to stand, filtering to obtain solid particles, and calcining the solid particles in a tube furnace under a high-purity argon atmosphere to obtain a graphite oxide-coated aluminum oxide composite material with high stamping mechanical strength synthesized by chemical bond induction; Furthermore, the aluminum salt in S1 is aluminum nitrate, aluminum chloride or aluminum sulfate, the mass percentage of aluminum salt to ammonia water is 97:3, the reaction is carried out at room temperature, the reaction time is 24 h, the calcination temperature is 800°C, the heating rate is 5°C / min, and the calcination is 6 h.
[0007] Furthermore, the inorganic binder of S2 is nitric acid water, the mass percentage of alumina powder to binder is 97:3, the calcination temperature is 500°C, the heating rate is 5°C / min, and the calcination is 4 h.
[0008] Furthermore, the acid solution of S3 is hydrochloric acid with a concentration of 2 M, a mass percentage of hydrochloric acid to aluminum oxide of 10:1, an etching temperature of 80° C., and a etching time of 30 min.
[0009] Furthermore, the mass percentage of graphite powder, sodium nitrate and acid solution in S4 is 2:1:90, the acid solution is concentrated sulfuric acid, and the mass percentage of potassium permanganate and graphite powder is 3:1.
[0010] Furthermore, in the S5, the mass ratio of ionized water to acid solution is 25:23, the heating temperature is 80° C., maintained for 30 min, and the strong oxidant is hydrogen peroxide.
[0011] Furthermore, the alcohol solution in S6 is ethylene glycol, the flash evaporation temperature is 220° C., and the polar solid-affinity groups are mainly active groups such as carboxyl and hydroxyl groups.
[0012] Furthermore, the mass percentage of the alumina particles with hydroxyl group defects in the S7 to the oxygen-rich graphite oxide is 10:1, the standing time is 48 h, the calcination temperature is 500° C., the heating rate is 3° C. / min, the calcination atmosphere is high-purity argon, and the calcination is 4 h.
[0013] A graphite oxide-coated alumina composite material with high stamping mechanical strength prepared by the chemical bond induced synthesis using the preparation method.
[0014] A graphite oxide-coated alumina composite material with high stamping mechanical strength synthesized by chemical bond induction is used in the preparation of catalyst carriers.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention synthesizes a composite material of graphite coated with an alumina carrier by induction of chemical bonds. During the molding process, the alumina carrier will form cracks and structural fragmentation on the surface and inside of the material due to the rich pore structure, resulting in a decrease in the mechanical strength of the stamping and a decrease in the performance. The present invention regulates the hydroxyl groups on the surface of the alumina material by etching with an acid solution to form a chemical group with a vacancy defect (mainly oxygen atoms). At the same time, on this basis, the surface of the graphite oxide is subjected to instant high-temperature oxidation to increase the surface oxygen-containing polar groups of the graphite oxide. In this case, the oxygen-rich groups of the graphite oxide will form covalent bonds or cross-linking with the defect sites in the alumina during the process of coating the alumina. At this time, the graphite oxide can not only improve the mechanical stamping strength of the alumina carrier by coating, but also form a similar bonding colloid effect, bonding and filling the holes on the surface of the alumina, forming the surface of the alumina material into a uniform whole, and improving the mechanical stamping strength of the alumina carrier; the preparation process of the present invention is easy to control, the process is simple, the cost is low, and it is suitable for industrial mass production; the prepared nanocomposite material has the characteristics of regular morphology and good uniformity. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0017] Figure 1 The XRD diagram of the graphite oxide-coated alumina composite material prepared by chemical bond induction in the present invention.
[0018] Figure 2 This is a SEM image of graphite oxide-coated alumina prepared in the present invention without using steps S3 and S6 (without surface modification of graphite oxide and alumina).
[0019] Figure 3 This is a SEM image of the graphite oxide-coated alumina composite material prepared by chemical bond induction in the present invention.
[0020] Figure 4The stamping mechanical strength of the graphite oxide coated alumina composite material prepared by chemical bond induction is compared with the stamping mechanical strength of the graphite oxide coated alumina composite material prepared without using the S3 and S6 steps (without surface modification of graphite oxide and alumina).
[0021] Figure 5 This is a SEM image of the graphite oxide-coated aluminum oxide composite material prepared by chemical bond induction in Example 2 of the present invention.
[0022] Figure 6 This is a SEM image of the graphite oxide-coated aluminum oxide composite material prepared by chemical bond induction in Example 3 of the present invention. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1 A method for preparing a graphite oxide-coated aluminum oxide composite material by chemical bond induction comprises the following steps.
[0025] S1. Dissolve 800 g of aluminum nitrate in 3 L of deionized water and stir to obtain solution A. Add 21.7 ml of aqueous ammonia to solution A and stir for 24 h. Filter and obtain aluminum hydroxide powder. Place the aluminum hydroxide powder in a tubular furnace under air atmosphere and calcine at a temperature of 800 °C. The heating rate is 5 °C / min and the calcination time is 6 h to obtain aluminum oxide powder.
[0026] S2. 800 g of alumina powder was mixed with 34.8 ml of nitric acid water in a high-speed mixer for 3 minutes, and then extruded and granulated in a twin-screw extruder (screw diameter 35 mm, aspect ratio 42, screw speed 150 rpm, temperature 200°C). The obtained alumina particles containing a binder were calcined in a tubular furnace at 500°C in an air atmosphere for 4 hours to remove organic matter to obtain alumina particles.
[0027] S3. Disperse 600 g of alumina particles in 70.8 mL of 2 M hydrochloric acid solution, maintain 80 °C, and react for 2 h to obtain alumina particles with hydroxyl group defects.
[0028] S4. Slowly add 2 g of graphite powder and 1 g of sodium nitrate into 50 mL of concentrated H2SO4, keep in an ice-water bath, stir for 1 h to obtain a solution, slowly add 6 g of potassium permanganate into the solution, keep in an ice-water bath and stir for 30 min, then heat the temperature to 35 °C and react for 2 h to obtain a mixed solution B.
[0029] S5. Slowly add 100 mL of deionized water to the mixed solution B, heat to 80 °C for 30 min, add 50 mL of deionized water, cool to room temperature, add hydrogen peroxide until no bubbles are generated, centrifuge, wash several times with 0.2 M dilute hydrochloric acid, anhydrous ethanol and deionized water, and vacuum freeze-dry for 24 h to obtain dark yellow graphite oxide.
[0030] S6. Disperse 2 g of reduced graphene oxide in 50 mL of ethylene glycol solution by ultrasonication and set aside. Heat the three-mouth flask to 220 °C by an electric heating jacket, and drip the dispersion of graphene oxide in ethylene glycol into the three-mouth flask at a rate of 1 mL / min through a dropping syringe. At the same time, draw air into the three-mouth flask through a vacuum pump to obtain graphite oxide in an oxygen-rich state.
[0031] S7. Add 600 g of alumina particles with hydroxyl group defects and 60 g of oxygen-enriched graphite oxide into 500 mL of ethylene glycol solution and let it stand for 48 h. Place the obtained solid particles in a tube furnace and calcine at 500°C with a heating rate of 3°C / min in a high-purity argon atmosphere for 4 h to obtain a composite material of graphite oxide-coated alumina with high stamping mechanical strength synthesized by chemical bond induction.
[0032] Reference Figure 1 The XRD pattern of the graphite oxide coated alumina composite material prepared by chemical bond induction shows that three broad diffraction peaks appear at 2θ = 36.2°, 44.6°, and 68.4°. By comparing with the XRD standard card of γ-Al2O3 (JCPDF NO. 29-0063), it is found that these three peaks belong to the (311), (400) and (440) crystal planes, respectively, indicating that alumina powder can be successfully prepared by the method of the present invention. At the same time, the characteristic peak of graphite oxide is found at about 22°, indicating that the method of the present invention successfully coats graphite oxide on the surface of alumina particles.
[0033] Reference Figure 2-3, SEM images of graphite oxide coated alumina prepared without using steps S3 and S6 of the present invention (without surface modification of graphite oxide and alumina) and SEM images of graphite oxide coated alumina composite materials prepared by chemical bond induction are shown. It can be seen from the figure that the surface of the graphite oxide coated alumina composite material prepared without using steps S3 and S6 has obvious cracks and channels, and is not uniform. The diameter of individual alumina is about 8 um. The surface of the graphite oxide coated alumina composite material prepared by chemical bond induction is uniform without obvious holes, and the individual alumina is aggregated into a whole through the cross-linking effect of chemical bonds, and the diameter is far greater than 8 um, indicating that the method of chemical bond induction in the present invention not only plays a coating guiding role, but also plays a role in bonding and cross-linking.
[0034] The graphite oxide-coated alumina composite material prepared by chemical bond induction as above was used as a catalyst carrier of 1 mm particles to test the stamping mechanical strength.
[0035] Preparation method: Add 600 g of alumina particles with hydroxyl group defects and 60 g of oxygen-enriched graphite oxide to 500 mL of ethylene glycol solution, let it stand for 48 hours, place the obtained solid particles in a tube furnace, calcine at 500°C, with a heating rate of 3°C / min, and calcinate in high-purity argon atmosphere for 4 hours to obtain a composite material of graphite oxide coated alumina with high stamping mechanical strength synthesized by chemical bond induction.
[0036] Test method: First, measure the particle diameter of each chemical bond induced graphite oxide coated alumina sample, and calculate the cross-sectional area. Secondly, place the chemical bond induced graphite oxide coated alumina sample vertically in a mechanical strength tester to test the maximum pressure value that each chemical bond induced graphite oxide coated alumina sample can withstand. Finally, based on the cross-sectional area of each alumina sample and the maximum pressure it withstands, calculate the maximum pressure value that each alumina sample can withstand. The chemical bond induced graphite oxide coated alumina sample was tested 20 times, and the average value was removed. From Figure 4 We found that the stamping mechanical strength of the alumina catalyst carrier synthesized by chemical bond induction is much higher than that of the alumina catalyst carrier not synthesized by chemical bond induction. The highest stamping mechanical strength of the alumina catalyst carrier not synthesized by chemical bond induction is 31.22 MPa, and the lowest stamping mechanical strength is 22.25 MPa; while the highest stamping mechanical strength of the alumina catalyst carrier synthesized by chemical bond induction is 40.12 MPa, and the stamping mechanical strength is 29.4 MPa. Therefore, the chemical bond induction synthesis method proposed in the present invention can solve the problem of decreased stamping mechanical strength of alumina during the molding process due to its rich pore structure.
[0037] Embodiment 2: The 800 g of aluminum nitrate in Example 1 was replaced by 800 g of aluminum chloride, and the remaining steps were the same as in Example 1 to obtain a chemical bond induced graphite oxide-coated aluminum oxide composite material.
[0038] Embodiment 3: The 800 g of aluminum nitrate in Example 1 was replaced with 800 g of aluminum sulfate, and the remaining steps were the same as in Example 1 to obtain a chemical bond induced graphite oxide-coated alumina composite material.
[0039] Figure 5 and Figure 6 They are SEM images of the nanoparticles of Example 2 and Example 3, respectively, and both obtained chemical bond-induced graphite oxide-coated alumina composite materials.
[0040] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a graphite oxide-coated alumina composite material with high stamping mechanical strength by chemical bond induction synthesis, characterized in that: The following steps are involved: S1. Dissolve aluminum salt in deionized water, stir to obtain solution A, add ammonia water to solution A, let stand, filter to obtain aluminum hydroxide powder, and calcine the aluminum hydroxide powder in a tube furnace under air atmosphere to obtain aluminum oxide powder; S2, adding an inorganic binder to the alumina powder, kneading it for multiple times, placing it in an extruder, drying and calcining it to obtain alumina particles; S3, etching the hydroxyl groups on the surface of the aluminum oxide particles by an acid solution to obtain aluminum oxide particles with chemical group defects; S4, adding graphite powder and sodium nitrate to the acid solution under ice-water bath conditions, slowly adding potassium permanganate, stirring, heating in a water bath to a certain temperature, and maintaining, to obtain a mixed solution B; S5, adding deionized water and a strong oxidant to the mixed solution B cooled to room temperature until no bubbles are generated, centrifuging, washing, and drying to obtain dark yellow graphite oxide; S6, dispersing graphite oxide in an alcohol solution, introducing polar oxygen-containing groups into the graphite oxide by an instant high-temperature oxidation method, and obtaining graphite oxide in an oxygen-rich state on the surface; S7, dispersing aluminum oxide particles with hydroxyl group defects in a deionized water solution, adding oxygen-enriched graphite oxide, allowing to stand, filtering to obtain solid particles, and calcining the solid particles in a tube furnace under a high-purity argon atmosphere to obtain a graphite oxide-coated aluminum oxide composite material with high stamping mechanical strength synthesized by chemical bond induction; The method for preparing a graphite oxide-coated alumina composite material with high stamping mechanical strength synthesized by chemical bond induction according to claim 1, characterized in that the aluminum salt in S1 is aluminum nitrate, aluminum chloride or aluminum sulfate, the mass percentage of aluminum salt to ammonia water is 97:3, the reaction is carried out at room temperature, the reaction time is 24 h, the calcination temperature is 800 ° C, the heating rate is 5 ° C / min, and the calcination is 6h.
2. The graphite oxide-coated alumina composite material with high stamping mechanical strength synthesized by chemical bond induction according to claim 1, characterized in that: The inorganic binder of S2 is nitric acid water, the mass percentage of alumina powder to binder is 97:3, the calcination temperature is 500°C, the heating rate is 5°C / min, and the calcination is 4 h.
3. The graphite oxide-coated alumina composite material with high stamping mechanical strength synthesized by chemical bond induction according to claim 1, characterized in that: The acid solution of S3 is hydrochloric acid with a concentration of 2 M, a mass ratio of hydrochloric acid to aluminum oxide of 10:1, an etching temperature of 80° C., and a etching time of 30 min.
4. The graphite oxide-coated alumina composite material with high stamping mechanical strength synthesized by chemical bond induction according to claim 1, characterized in that: The mass ratio of graphite powder, sodium nitrate and acid solution in S4 is 2:1:90, the acid solution is concentrated sulfuric acid, and the mass ratio of potassium permanganate to graphite powder is 3:
1.
5. The graphite oxide-coated alumina composite material with high stamping mechanical strength synthesized by chemical bond induction according to claim 1, characterized in that: The mass ratio of ionized water to acid solution in S5 is 25:23, the heating temperature is 80° C., maintained for 30 min, and the strong oxidant is hydrogen peroxide.
6. The graphite oxide-coated alumina composite material with high stamping mechanical strength synthesized by chemical bond induction according to claim 1, characterized in that: The alcohol solution in S6 is ethylene glycol, the flash evaporation temperature is 220° C., and the polar solid-affinity groups are mainly active groups such as carboxyl and hydroxyl groups.
7. The graphite oxide-coated alumina composite material with high stamping mechanical strength synthesized by chemical bond induction according to claim 1, characterized in that: The mass percentage of the alumina particles with hydroxyl group defects in the S7 to the oxygen-rich graphite oxide is 10:1, the standing time is 48 h, the calcination temperature is 500° C., the heating rate is 3° C. / min, the calcination atmosphere is high-purity argon, and the calcination is 4 h.
8. A graphite oxide-coated alumina composite material with high stamping mechanical strength prepared by chemical bond induced synthesis using the preparation method according to any one of claims 1 to 8.
9. Use of the graphite oxide-coated alumina composite material with high stamping mechanical strength synthesized by chemical bond induction according to claim 9 in the preparation of a catalyst carrier.
Citation Information
Patent Citations
Process for preparing alumina carrier
CN101450327A
Graphene / nano-aluminum compound and preparation method thereof
CN103723705A
Method for preparing alumina / graphene core-shell structured composite material
CN108675772A
Manufacturing method of alumina-graphene composites with excellent wear resistance
KR1020170006002A